Thermoluminescence of secondary glow peaks in carbon-doped aluminium oxide - Seneza, Cleophace (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2014)
Carbon-doped aluminium oxide, Î±-Alâ‚‚Oâ‚ƒ : C, is a highly sensitive luminescence dosimeter. The high sensitivity of Î±-Alâ‚‚Oâ‚ƒ : C has been attributed to large concentrations of oxygen vacancies, F and Fâ º centres, induced in the material during its preparation. The material is prepared in a highly reducing atmosphere in the presence of carbon. In the luminescence process, electrons are trapped in F-centre defects as a result of irradiation of the material. Thermal or optical release of trapped electrons leads to emission of light, thermoluminescence (TL) or optically stimulated light (OSL) respectively. The thermoluminescence technique is used to study point defects involved in luminescence of Î±-Alâ‚‚Oâ‚ƒ : C. A glow curve of Î±-Alâ‚‚Oâ‚ƒ : C, generally, shows three peaks; the main dosimetric peak of high intensity (peak II) and two other peaks of lower intensity called secondary glow peaks (peaks I and III). The overall aim of our work was to study the TL mechanisms responsible for secondary glow peaks in Î±-Alâ‚‚Oâ‚ƒ : C. The dynamics of charge movement between centres during the TL process was studied. The phototransferred thermoluminescence (PTTL) from secondary glow peaks was also studied. The kinetic analysis of TL from secondary peaks has shown that the activation energy of peak I is 0.7 eV and that of peak III, 1.2 eV. The frequency factor, the frequency at which an electron attempts to escape a trap, was found near the range of the Debye vibration frequency. Values of the activation energy are consistent within a variety of methods used. The two peaks follow first order kinetics as confirmed by the TM-Tstop method. A linear dependence of TL from peak I on dose is observed at various doses from 0.5 to 2.5 Gy. The peak position for peak I was also independent on dose, further confirmation that peak I is of first order kinetics. Peak I suffers from thermal fading with storage with a half-life of about 120 s. The dependence of TL intensity for peak I increased as a function of heating rate from 0.2 to 6ÂºCsâ »Â¹. In contrast to the TL intensity for peak I, the intensity of TL for peak III decreases with an increase of heating rate from 0.2 to 6ÂºCsâ »Â¹. This is evidence of thermal quenching for peak III. Parameters W = 1.48 Â± 0:10 eV and C = 4 x 10Â¹Â³ of thermal quenching were calculated from peak III intensities at different heating rates. Thermal cleaning of peak III and the glow curve deconvolution methods confirmed that the main peak is actually overlapped by a small peak (labeled peak IIA). The kinetic analysis of peak IIA showed that it is of first order kinetics and that its activation energy is 1:0 eV. In addition, the peak IIA is affected by thermal quenching. Another secondary peak appears at 422ÂºC (peak IV). However, the kinetic analysis of TL from peak IV was not studied because its intensity is not well defined. A heating rate of 0.4ÂºCsâ »Â¹ was used after a dose of 3 Gy in kinetic analysis of peaks IIA and III. The study of the PTTL showed that peaks I and II were regenerated under PTTL but peak III was not. Various effects of the PTTL for peaks I and II for different preheating temperatures in different samples were observed. The effect of annealing at 900ÂºC for 15 minutes between measurements following each illumination time was studied. The effect of dose on secondary peaks was also studied in this work. The kinetic analysis of the PTTL intensity for peak I showed that its activation energy is 0.7 eV, consistent with the activation energy of the normal TL for peak I. The PTTL intensity from peak I fades rapidly with storage compared with the thermal fading from peak I of the normal TL. The PTTL intensity for peak I decreases as a function of heating rate. This decrease was attributed to thermal quenching. Thermal quenching was not observed in the case of the normal TL intensity. The cause of this contrast requires further study.
Keywords: Thermoluminescence; Aluminum oxide; Thermoluminescence dosimetry